Erlernen von Priorisierungskompetenz medizinischer Hilfeleistungen am Beispiel der Sichtung: Vergleich zweier Lehrstrategien - Lütcke, Björn; Birkholz, Torsten; Dittmar, M. S.; Breuer, G. (Notfall und Rettungsmedizin, 2019)
Background: Prioritisation competence has relevance beyond emergency medical education and training. Two teaching strategies were compared in this study on the basis of the triage of injured persons. The aim was to describe the teaching method that successfully convey “priority” to novices. Methodology: 96 students categorised case vignettes after an introductory lecture and joint development of allocation categorisation (SK) using the “Amberg-Schwandorf-Algorithmus für die Vorsichtung” (ASAV) in a four-member team. In the traditional teaching method (TL), the SK was only voiced by one participant as the result of his own assessment. In a new teaching approach to be compared here, the SK was named, justified and discussed (reasoning reflection; BR). Finally, an individual success check (EK 1) and 14 days later (EK 2) (long-term effect) were carried out. In addition, subjective learning success was recorded. Results: 1920 initial assessment procedures were recorded in EK 1. Correctness was 69.6% (TL) and 70.5% (BR), the undertriage 25.9% and 26.8%, the overtriage 4.5% and 2.7%, respectively. In the delayed test with 740 initial assessment procedures, the correctness was 67.38% and 72.5% respectively, the lower triage 21.9 vs. 15.94%, the upper triage 10.71 vs. 11.56%. No method was statistically superior (χ2 test). The teaching method with reasoned reflection led to a higher subjective learning satisfaction. Discussion: Both teaching/learning conditions led to comparable results. With regard to the quality of the sighting results, the performance would be rather unsatisfactory. The medical complexity of a caution algorithm is rather low in comparison to other, e.g. intensive care decision situations, so that limited expert knowledge would generally be sufficient for successful implementation. The learning satisfaction was higher with justification reflection. The hypothesis that the learning method with the higher learning satisfaction produces a more lasting learning effect and a higher transfer performance should be the subject of further investigations.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Cooperative learning; Curriculum; Mass casualty attack; Rescue services; Teaching methods